Neonatal visual assessment in congenital heart disease: A pilot study. (25th August 2022) - Ergul, Ayca; Feldmann, Maria; Hagmann, Cornelia; Bernet, Vera; Knirsch, Walter; Latal, Beatrice
Abstract: This study assessed neonatal visual maturity in infants with congenital heart disease (CHD) and its predictive value for neurodevelopmental outcomes. Neonates with CHD underwent a standardized visual assessment before and after cardiopulmonary bypass surgery. Visual maturity was rated as normal versus abnormal by means of normative reference data. Twelve-month neurodevelopment was assessed with the Bayley-III. Twenty-five healthy controls served as the reference group. Neonatal visual assessment was performed in five neonates with CHD preoperatively and in 24 postoperatively. Only postoperative assessments were considered for further analysis. Median [IQR] age at assessment was 27.0 [21.5, 42.0] days of life in postoperative neonates with CHD and 24.0 [15.0, 32.0] in controls. Visual performance was within reference values in 87.5% in postoperative CHD versus 90.5% in healthy controls ( p = 1.0). Visual maturity was not predictive of neurodevelopment at 12 months. These results demonstrate the limited feasibility and predictive value of neonatal visual assessments in CHD.